Consumption of non-sugar sweeteners by Brazilian adolescents and adults in 2017–2018: Socioeconomic distribution and food sources - Luisa Gazola Lage; Claudia Cristina Gonçalves Pastorello; Marcos Anderson Lucas da Silva; Vanessa dos Santos Pereira Montera; Daniela Silva Canella; Camila Aparecida Borges; Maria Laura da Costa Louzada (PLoS ONE, 2025)
Non-sugar sweeteners are food additives frequently used as sugar substitutes. Recent evidence has demonstrated harmful health effects of non-sugar sweeteners. However, studies on the consumption of these substances are scarce. This study aimed to describe the consumption of non-sugar sweeteners by Brazilian adolescents and adults in 2017–2018, using data from the most recent nationally representative dietary survey. This cross-sectional study analyzed individual food intake data from the 2017–2018 Household Budget Survey, collected using a 24-hour dietary recall. We assessed the prevalence of consumers of: (i) tabletop sweeteners, (ii) diet/light-labeled products containing non-sugar sweeteners, (iii) non-sugar sweeteners present in foods, and (iv) any source of non-sugar sweeteners. Prevalence estimates were stratified by sex, age group (adolescents ≥10 to <18 years, adults 18 to <60 years, and elderly ≥60 years), and income quintiles. Additionally, food sources, types of sweeteners, and patterns of concurrent sweetener consumption were evaluated. Overall, 20.6% of Brazilians consumed non-sugar sweeteners. Prevalence was higher prevalence among women (22.7%), older adultes (27.0%), adolescents (24.4%), and individual in the highest income quintile (30.7%). Tabletop sweeteners were the main source (38.2%), followed by artificially sweetened beverages, including juices (25.3%), and yogurts or dairy drinks (25.1%). Most individuals consumed a combination of sweeteners, primarily acesulfame K, sucralose, and aspartame. Non-sugar sweeteners are widely consumed in Brazil, particularly among specific demographic groups, with tabletop sweeteners and sweetened beverages as the main sources. These findings provide essential insights to guide public health policies and regulatory discussions.